Human CAR NK Cells: A New Non-viral Method Allowing High Efficient Transfection and Strong Tumor Cell Killing - Ingegnere, Tiziano; Mariotti, Francesca Romana; Pelosi, Andrea; Quintarelli, Concetta; De Angelis, Biagio; Tumino, Nicola; Besi, Francesca; Cantoni, Claudia; Locatelli, Franco; Vacca, Paola; Moretta, Lorenzo (Frontiers in Immunology, 2019)
CAR-NK cells may represent a valuable tool, complementary to CAR-T cells, in adoptive immunotherapy of leukemia and solid tumors. However, gene transfer to human NK cells is a challenging task, particularly with non-virus-based techniques. Here, we describe a new procedure allowing efficient electroporation-based transfection of plasmid DNA, including CAR and CCR7 genes, in resting or cytokine-expanded human NK cell populations and NK-92 cell line. This procedure may offer a suitable platform for a safe and effective use of CAR-NK cells in adoptive immunotherapy of cancer.